The long-term collateral consequences of juvenile justice involvement for females - Schweer-Collins, Maria L.; Dierkhising, Carly B.; Leve, Leslie D. (Frontiers in Psychology, 2024)
Females are the fastest growing justice involved population in the United States, yet there is relatively little empirical research on the collateral consequences of juvenile justice involvement specifically for females. A growing body of empirical research underscores the linkages between juvenile justice involvement and negative health and psychosocial outcomes, both in the short and long term. The current study describes the long-term collateral consequences of juvenile justice involvement for females previously involved in the juvenile justice system, drawing from a longitudinal dataset of 166 women who were initially recruited in adolescence due to chronic and severe justice system involvement. Participants were 15 years-old on average at study enrollment and 35 years-old on average at the current assessment. This paper describes the adolescent and adult experiences of the sample, therefore depicting the developmental trajectories of risk and protective factors for females involved with juvenile justice. As adults, 73% of the sample experienced arrest and 36% experienced incarceration. High rates of mental and physical health problems were reported, including that 50% of the sample met diagnostic criteria for posttraumatic stress disorder. Over 400 children were born to the sample, with high rates of documented intergenerational child welfare involvement. Study findings are discussed in the context of best practices for supporting adolescent girls involved with the juvenile justice system.